Postural control in children: Coupling to dynamic somatosensory information - Barela, José A. [UNESP]; Jeka, John J.; Clark, Jane E. (My University, 2003)
The purpose of this investigation was to determine whether the coupling between dynamic somatosensory information and body sway is similar in children and adults. Thirty children (4-, 6-, and 8-year-olds) and 10 adults stood upright, with feet parallel, and lightly contacting the fingertip to a rigid metal plate that moved rhythmically at 0.2, 0.5, and 0.8 Hz. Light touch to the moving contact surface induced postural sway in all participants. The somatosensory stimulus produced a broadband frequency response in children, while the adult response was primarily at the driving frequency. Gain, as a function of frequency, was qualitatively the same in children and adults. Phase decreased less in 4-year-olds than other age groups, suggesting a weaker coupling to position information in the sensory stimulus. Postural sway variability was larger in children than adults. These findings suggest that, even as young as age 6, children show well-developed coupling to the sensory stimulus. However, unlike adults, this coupling is not well focused at the frequency specified by the somatosensory signal. Children may be unable to uncouple from sensory information that is less relevant to the task, resulting in a broadband response in their frequency spectrum. Moreover, higher sway variability may not result from the sensory feedback process, but rather from the children's underdeveloped ability to estimate an internal model of body orientation.
Keywords: Development; Posture; Sensorimotor; Somatosensation; Touch; age; aged; body equilibrium; body posture; child; controlled study; human; human experiment; male; normal human; priority journal; sensorimotor function; somatosensory stimulation; spatial orientation; touch; Adult; Age Factors; Brain; Child; Child, Preschool; Humans; Male; Proprioception